Terpyridine‐Based 3D Discrete Metallosupramolecular Architectures. Issue 14 (25th February 2022) - Yu, Xiujun; Guo, Chenxing; Lu, Shuai; Chen, Zhi; Wang, Heng; Li, Xiaopeng
Abstract: Terpyridine (tpy)‐based 3D discrete metallosupramolecular architectures, which are often inspired by polyhedral geometry and the biological structures found in nature, have drawn significant attention from the community of metallosupramolecular chemistry. Because of the linear tpy–M(II)–tpy connectivity, the creation of sophisticated 3D metallosupramolecules based on tpy remains a formidable synthetic challenge. Nevertheless, with recent advancement in ligand design and self‐assembly, diverse 3D metallosupramolecular polyhedrons, such as Platonic solids, Archimedean solids, prims as well as Johnson solids, have been constructed and their potential applications have been explored. This review summarizes the progress on tpy‐based discrete 3D metallosupramolecules, aiming to shed more light on the design and construction of novel discrete architectures with molecular‐level precision through coordination‐driven self‐assembly. Abstract : This review summarizes the recent progress on terpyridine‐based discrete 3D metallosupramolecules, aiming to shed more light on the design and construction of novel discrete architectures with molecular‐level precision through coordination‐driven self‐assembly. Three major strategies including direct self‐assembly, stepwise self‐assembly, and multicomponent self‐assembly are highlighted with the focus on the control over the size and shape of 3D metallosupramolecules.